Improving general practitioners’ approaches to functional somatic syndromes: a pilot training program with a focus on compassion and communication - Gonthier Ariane; Linder Audrey; Sommer Johanna; Despland Jean-Nicolas; Ambresin Gilles (BMC Medical Education)
Abstract Background Functional somatic syndromes are common in primary care and represent a challenge for general practitioners (GPs), with a risk of deterioration in the doctor-patient relationship, and of compassion fatigue on the part of the physician. Little is known about how to teach better management of these symptoms. Methods The aim of our scientific team was to develop a training session about functional somatic syndromes for GPs, with the objective to improve the therapeutic attitude of the participants. The first session of the training was constructed as a pilot session, followed by a qualitative study to complete content validation. The educational framework of the training session is multimodal and includes theory on the pathophysiology of functional somatic syndromes, communication skills, and introspective learning including an introduction to compassion meditation. 20 physicians attended the pilot training session. 10 of them participated in the qualitative study. The qualitative study consisted of five individual semi-structured interviews and one focus group of five persons, investigating the impact of the training session on the clinical practices, as perceived by the participants. The interviews were analysed through an inductive method inspired by Malterud’s systematic text condensation strategy. Results We identified three main themes in the responses of the participants: (1) the crucial issue of putting a name to chronic psychosomatic suffering; (2) the importance of self-compassion for physicians; (3) changes in therapeutic attitude fostering a reconciliation between “self” and “care”. Participants expressed a need for more regular meetings of this type. The opportunity to share their negative feelings about therapeutic relationship within a peer group, with compassionate supervision of the trainers, seemed to play an important role in the improvement of their self-compassion Conclusion A multimodal teaching session seems to help the physicians to feel more comfortable and competent when treating patients with functional somatic syndromes. Including compassion meditation in the teaching seems a promising tool to prevent compassion fatigue.